Correlation Between Insulin Therapy and Quality of Life in Patients with Type 2 Diabetes Mellitus and Hypertension at Sunan Kudus Islamic Hospital - Sinta Putri Arifati; Eko Retnowati; Intan Adevia Rosnarita; Intan Setyaningrum (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to examine the relationship between insulin therapy effectiveness and quality of life among patients with type 2 diabetes mellitus and comorbid hypertension at Sunan Kudus Islamic Hospital. It hypothesizes that glycemic and blood pressure control are significantly associated with patients’ quality of life. Research Method: This quantitative observational-analytical study employed a cross-sectional design. A total of 105 patients were selected through purposive sampling. Quality of life was assessed through interviews using the validated EQ-5D-5L questionnaire, while random blood glucose and blood pressure data were obtained from medical records. Univariate analysis and the Mann–Whitney test were performed using SPSS version 27. Results and Discussion: Most respondents had ineffective control of random blood glucose (55.2%), controlled blood pressure (57.1%), and good quality of life (63.8%). Mann–Whitney analysis showed significant associations between random blood glucose, blood pressure, and quality of life (p = 0.001). These findings indicate that metabolic and blood pressure control are important determinants of patients’ perceived health status. Implications: Healthcare providers should strengthen insulin monitoring, patient education, adherence support, and the integration of diabetes–hypertension management. Originality: This study simultaneously evaluates insulin effectiveness, blood pressure control, and quality of life among patients with T2DM and hypertension in a hospital-based setting in Indonesia.